The Knowledge Economy and Human Capital: A Literature Review - Al-Amrani, Halima Sharif Muhammad; Al-Rabghi, Reem Ali; Mujallid, Rabab Abdulrahman (Journal of Economic, Administrative and Legal Sciences, 2025)
The current study aims to conduct a comprehensive literature review on the topic of the knowledge economy and human capital, exploring the development of related concepts and research trends in both Arabic and international scholarly output during the period (1990–2024). The study adopts a descriptive-analytical methodology using content analysis, with data collected from seven Arabic and international databases and search engines by identifying relevant keywords and analyzing associated titles and abstracts. The results revealed a range of research topics covered in the literature, most notably: the evolution of the concepts of “knowledge economy” and “human capital,” the role of human capital in building a knowledge-based economy, the significance of education, training, and scientific research in enhancing knowledge capital, and the relationship between digital transformation and human capital formation. The study also reviewed relevant conferences, workshops, and scientific associations, and tracked the digital index of scholarly output through selected databases and search engines. Findings indicate a notable increase in related academic production during the period (2014–2024) compared to (1990–2013), with the number of international publications in Google Scholar reaching approximately 54,600, versus only 349 Arabic publications. Furthermore, the review revealed a scarcity of conferences and workshops addressing the intersection of the two themes in Arabic literature, while ProQuest ranked second with 1,090 studies after Google Scholar. The study recommends strengthening investment in human capacity development, education, and innovation, given their critical role in supporting the knowledge economy and achieving sustainable growth.
Keywords: Knowledge economy; human capital